The Servant of YHWH during the Babylonian Exile: An Extension of an Existing Israelite Mission, or a New Departure? - Ignatious Kunnumpurathu Paul (Wrocławski Przegląd Teologiczny)
The question of how Israel looked outward historically is a long-standing one. Is there a genuine tradition of proselytism in the Old Testament? Although there are indications of Abraham’s proselytism and his belief that the blessings of God would extend through him to all nations, the missionary dimension was almost non-existent through the centuries which followed. Israel was engaged in virtually continuous wars against its neighbours, both to consolidate its borders and ensure its survival, and consequently became focussed on itself. The emergence of the Servant of YHWH in the sixth century B.C. represents a drastic shift to an altogether more altruistic orientation. To appreciate the depth of the missionary or salvific undertaking of the Servant, the various dimensions of his identity, as unfolded in the texts of Isaiah, will be explored. His liberating mission was directed towards the people of Israel and to the gentiles, as is seen in the four Servant Songs in Deutero-Isaiah, where he is depicted as: a) Servant, the Executor of Social Justice (Isa 42:1–4); b) Servant, the Mediator between YHWH and His peoples (Isa 49:1–6), c) Servant, the Preacher of Liberation (Isa 50:4–9), d) Servant, the Promulgator of Salvation (Isa 52:13–53:12). The figure we encounter in the Servant Songs is really unique in the history of Israel, and stands out in striking contrast to all the other prominent figures we might consider in the nation’s history. His liberating mission during the Babylonian exile is also unparalleled. There are therefore ample grounds for concluding that the Servant’s mission to extend salvation to both Israel and the gentiles is not an extension of the existing Israelite mission, but is of an entirely new order.